The Comparison of Quilting Sutures and Conventional Sutures for Flap Fixation in Modified Radical Mastectomy for Seroma Formation: A Randomized Controlled Trial - Khan, Fayaz; Qureshi, Usman; Rasheed, Gohar; Babar, Hamza; Satti, Arslan Arshad; Khan, Zakir (Indus Journal of Bioscience Research, 2025)
Background: Seroma is a frequent postoperative complication in modified radical mastectomy (MRM) surgery that may cause patient discomfort, extended hospitalization, and adjuvant therapy delay. A number of methods, such as quilting sutures, have been suggested to stop the formation of seroma by eliminating dead space and decreasing fluid accumulation. Objective: To evaluate the efficacy of quilting sutures in reducing seroma formation compared to conventional sutures in patients undergoing modified radical mastectomy. Patients and Methodology: It is a randomized controlled trial conducted between 17 February to 17 June at the Holy Family Hospital in Rawalpindi. It comprised 60 female patients receiving MRM to treat carcinoma breast wherein 30 patients in each group were involved. Group A had quilting suture and Group B had conventional suture. The primary results were the occurrence of seroma formation but the secondary results were the drain output, the drainage time and postoperative complications. The data analysis was done using SPSS version 23.0, and the p-value of less than 0.05 was considered to be statistically significant. Results: The study population had mean age of 51.53 years with standard deviation of 8.49. The incidence of seroma was 3.3 percent in quilting group (Group A) versus 26.7 percent in conventional suture group (Group B) and the difference between them was statistically significant (p = 0.026). The mean length of stay of the drains inserted was much lower in Group A (3.93 ± 0.83 days) than in Group B (6.00 ± 0.74 days), and the overall drain output was much lower in Group A (93.00 ± 7.96 ml) than in Group B (121.87 ± 11.98 ml) (p = 0.01). The two groups did not exhibit any significant difference in terms of age, BMI, pain and shoulder mobility. Conclusion: Quilting sutures significantly reduce seroma formation in modified radical mastectomy compared to conventional sutures, with fewer aspirations and shorter drainage duration, making it a valuable technique for seroma prevention.